(untitled) (KULT_online, 2013)
Visual Communication is a field that has the greatest of heterogeneity in its disciplines as well as in its research methods. This anthology brings together approaches from communication science, media anthropology, psychology, journalism, history, and German philology. It concentrates on qualitative and quantitative research as well as on the genesis of material and its analyses. As soon as the reader has grasped the concept of the volume, it serves as a source rich in ideas and methods and of amazing depth.